Attributes of analgesics for emergency pain relief: results of the Consensus on Management of Pain Caused by Trauma Delphi initiative. (February 2020) - Porter, Keith; Morlion, Bart; Rolfe, Mark; Dodt, Christoph
Abstract : Objectives: Management of pain is suboptimal in many prehospital and emergency department settings, and European guidelines are lacking. We carried out the Consensus On Management of PAin Caused by Trauma (COMPACT) Delphi initiative to gain insights into the factors physicians consider important when selecting analgesics for trauma pain. Patients and methods: A pan-European panel of experts in emergency medicine or pain ( N = 31) was recruited to participate in the COMPACT Delphi initiative. In round 1, panelists supplied free-text responses to an open question about the attributes of analgesics for emergency pain relief favored by physicians. Common themes were consolidated into factors. In round 2, factors rated important by more than 75% of the panel were taken forward into round 3. In round 3, the point at which the consensus was achieved was defined a priori as at least 75% of panelists agreeing or strongly agreeing that a factor was important. Results: Twenty-nine experts participated, representing 12 European countries and with a mean (SD) of 20 (8.6) years of clinical experience. Most worked in an emergency department (79.3%). The consensus was achieved for 10 factors that were important to consider when selecting analgesics for trauma pain relief. The highest level of consensus was achieved for 'efficacy' (100%), followed by 'safety and tolerability' (96.6%), and 'ease of use' (93.1%). Conclusion: These findings may facilitate the development of evidence-based guidelines supporting the provision of pain management in prehospital, emergency department, and critical care settings. Abstract : Supplemental Digital Content is available in the text.